2004
DOI: 10.1081/css-200030368
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation and Distribution in Oil Crops

Abstract: To ascertain the level of pollution and the way the heavy metals enter oil crops, soil, and plant samples were taken at different distances from the source of pollution, the Non-Ferrous-Metal Works (NFMW) near Plovdiv (0.5 and 15 km). The contents of the heavy metals in the plant material (roots, stems, leaves, seeds, fruit shell) and sunflower oil and rapeseed oil were determined. The quantitative measurements were carried out with inductively coupled plasma emission spectrometer. Peanuts (Arachis hypogaea L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
0
21
1
Order By: Relevance
“…Cadmium, Cu, and Pb distribution in individual sunflower organs has also been studied by Angelova, Ivanova, and Ivanov (2004). They showed the following metal distribution in sunflowers tested on a metal contaminated field: leaves > roots > stem > seeds > fruit shell.…”
Section: Metal Distribution In Individual Organs Of M 4 Sunflower Mutmentioning
confidence: 98%
“…Cadmium, Cu, and Pb distribution in individual sunflower organs has also been studied by Angelova, Ivanova, and Ivanov (2004). They showed the following metal distribution in sunflowers tested on a metal contaminated field: leaves > roots > stem > seeds > fruit shell.…”
Section: Metal Distribution In Individual Organs Of M 4 Sunflower Mutmentioning
confidence: 98%
“…Studies have shown that the accumulation of contaminants or nutrients by plants varies greatly among crops and cultivars and also differs between different parts of a plant (Kurz et al 1999;Liu et al 2007). Seeds and fruits generally accumulate metals at lower concentrations than leaves or roots (McLaughlin et al 1996(McLaughlin et al , 1999Wenger et al 2002a;Angelova et al 2004;Liu et al 2007). For example, maize seed produced on contaminated land may be suitable for animal feed (Wenger et al 2002a), while the stems and leaves could be used for non-food purposes such as bioenergy production (Meher et al 1995;Licht and Isebrands 2005;Amon et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Some of these elements, such as rare earth elements, derive from the underlying rock and are therefore related to the geographical origin (Bandoniene, Zettl, Meisel, & Maneiko, ). On the other hand, environmental conditions, that is, air and soil pollution can significantly influence the content of elements, especially heavy metals in the edible oils (Angelova, Ivanova, & Ivanov, ).…”
Section: Resultsmentioning
confidence: 99%